2014
DOI: 10.1186/2193-1801-3-509
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis-associated aortitis: a case report and literature review

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune inflammatory disorder that primarily affects the synovial joints. Rheumatoid vasculitis (RV) is an extra-articular manifestation of RA, and its association with aortitis is rare and not widely recognised. Here, we report the case of a 69-year-old woman with RA-associated aortitis and review the literature on rheumatoid aortitis. The mean oral steroid dose administered to RA-associated aortitis patients was 46.3 mg/day prednisolone (PSL). In our patient, the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Our patient was 54 years old. The mean age of patients at diagnosis of aortitis in a literature review was 56±15.2 years old 6 . RV commonly affects small and medium sized vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient was 54 years old. The mean age of patients at diagnosis of aortitis in a literature review was 56±15.2 years old 6 . RV commonly affects small and medium sized vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The association of aortitis with RV is not widely recognized. However, many authors reported an association of RA with aortitis 6 . Our patient had a lesion typical of vasculitis of the aorta on his chest CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Less common manifestations are scleritis (0.3-6.3% incidence), pericarditis (<10% incidence), aortitis, pulmonary vasculitis and necrotizing glomerulonephritis (8%). A case report and literature review by Kanoko S et al reviewed 45 cases of active noninfectious aortitis seen among 513 consecutive ascending aortic resections, of which approximately 4% were RA patients [5][6][7][8]. Although common extra-articular manifestations are skin lesions, a clinician should also look for cardiac and pulmonary manifestation expecially if there is presence of concerning symptoms which are not otherwise explained.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid vasculitis may suspect on symptoms of rash, skin ulcers, numbness or tingling of the hands or feet, weakness in a hand or foot, cough and shortness of breath, chest pain, abdominal pain, or stroke symptoms [12].…”
Section: Diagnosismentioning
confidence: 99%
“…A blood test for specific antibodies that are directed against the inner layer of blood vessels (endothelial cells) are present in approximately 75% of patients with RV compared to only 15 to 20% of those with RA alone. Therefore, this blood test may be checked regularly in patients with any of these new or worsened symptoms [12].…”
Section: Laboratory Testsmentioning
confidence: 99%